Reductions in social anxiety during treatment predict lower levels of loneliness during follow-up among individuals with social anxiety disorder. (March 2021) - O'Day, Emily B.; Butler, Rachel M.; Morrison, Amanda S.; Goldin, Philippe R.; Gross, James J.; Heimberg, Richard G.
Highlights: Individuals with social anxiety disorder (SAD) are at elevated risk for loneliness. We examined loneliness in a randomized controlled trial of two treatments for SAD. Individuals who received treatment were less lonely than waitlist controls. Treatment changes in social anxiety predicted lower loneliness during follow-up. Treatment changes in loneliness predicted lower social anxiety during follow-up. Abstract: Introduction: Individuals with social anxiety disorder (SAD) are at elevated risk of loneliness, yet little research has examined loneliness in this population. Cognitive-behavioral group therapy (CBGT) and mindfulness-based stress reduction (MBSR) have demonstrated efficacy in treating SAD, yet research has not examined whether they lead to reductions in loneliness. Methods: This sample comprised 108 individuals with SAD who were randomized to CBGT, MBSR, or a waitlist control (WL); WL participants were re-randomized to CBGT or MBSR following WL. Assessments were completed pre- and post-treatment, and 3-, 6-, 9-, and 12-month follow-up assessments. Results: Compared to WL, individuals in CBGT and MBSR were less lonely at post-treatment; there was no difference between treatments after treatment or during follow-up. Greater reductions in social anxiety from pre- to post-treatment predicted lower levels of loneliness during follow-up. Greater reductions in loneliness from pre- to post-treatment also predicted lower levels of social anxiety during follow-up. Discussion: Individuals who experience reductions in their social anxiety during treatment may also feel less lonely following treatment. Reductions in loneliness also lead to improvements in social anxiety. Future research should continue to examine the relationship between social anxiety and loneliness and how interventions for SAD may help reduce loneliness.